α-Tocopherol loaded thermosensitive polymer nanoparticles: preparation, in vitro release and antioxidant properties - Quintero,Cirley (2016)
Abstract α-Tocopherol is the most bioavailable and active compound found in vitamin E with potential application in pharmaceutical, alimentary and cosmetic industries. However, its low solubility in aqueous medium and environmental instability limit its dosage. In this paper, we report the preparation of α-tocopherol loaded nanoparticles (TOC-NP) based on amphiphilic thermosensitive triblock copolymers PNIPAM-b-PCL-b-PNIPAM. The nanoparticles exhibited a core – shell structure, were positively charged and presented average diameters below 300 nm. TOC-NP presented controlled release of α-tocopherol at room temperature along 140h, and exhibited antioxidant properties in aqueous medium.